The Role of Taxation Knowledge on Individual Taxpayer Compliance in Paying Rural and Urban Land and Building Tax - Putri, Kartika Pratiwi; Yulianti, Maria Lusiana; Roswinna, Winna; Jayadinata, Fadilah (Journal of Innovation in Management, Accounting and Business, 2025)
This research aims to understand the Tax Knowledge of Individual Taxpayers for Rural and Urban Land and Building Tax in Dago Village, understand the Compliance of Individual Taxpayers for Rural and Urban Land and Building Tax in Dago Village, and understand the role of Tax Knowledge on Individual Taxpayer Compliance in Paying Rural and Urban Land and Building Tax in Dago Village, Coblong District, Bandung City. The research method used is Quantitative with descriptive and verificative approaches, with the sample consisting of 100 Individual Taxpayers for Rural and Urban Land and Building Tax in the Dago Village area, selected from a total population of 6,137 in 2023. The analysis tool used is Simple Linear Regression Analysis with the assistance of IBM SPSS 28 software. Based on the t-test results conducted by the researcher, the Tax Knowledge Variable plays a role in Individual Taxpayer Compliance, and the Simple Linear Regression Analysis results show that the higher the level of Tax Knowledge, the higher the level of Individual Taxpayer Compliance in Paying Rural and Urban Land and Building Tax in Dago Village